Learning from the Cultural Legacy: Traditional Learning Strategy of Basandi Syara’ and Syara’ Basandi Kitabullah in the Ulu Ambek Dance - Ridho, Muhammad; Daryusti; Efi, Agusti; Agustina (Universitas Jambi, Indonesia, 2025)
This research analyzes Ulu Ambek dance’s presentation and explores the adat’s symbolic meaning: